Recellularized rat testis scaffolds with embryoid bodies cells: a promising approach for tissue engineering - Batista, Vitória Frias; de Sá Schiavo Matias, Gustavo; Carreira, Ana Claudia Oliveira; Smith, Lawrence Charles; Rodrigues, Rafaela; Araujo, Michelle Silva; Souza Silva, Dara Rubia; Moraes, Felipe de Jesus; Garcia, Joaquim Mansano [UNESP]; Miglino, Maria Angelica (Taylor & Francis, 2022)
Tissue engineering is gaining use to investigate the application of its techniques for infertility treatment. The use of pluripotent embryonic cells for in vitro production of viable spermatozoa in testicular scaffolds is a promising strategy that could solve male infertility. Due to cell–extracellular matrix (ECM) interactions, here we aim to investigate the differentiation of embryoid bodies (EBs) in cultured into decellularized rat testis scaffolds. Decellularized testis (P = 0.019) with a low concentration of gDNA (30.58 mg/ng tissue) was obtained by sodium dodecyl sulfate perfusion. The structural proteins (collagens type I and III) and the adhesive glycoproteins of ECM (laminin and fibronectin) were preserved according to histological and scanning electron microscopy (SEM) analyses. Then, decellularized rat testis were cultured for 7 days with EB, and EB mixed with retinoic acid (RA) in non-adherent plates. By SEM, we observe that embryonic stem cells adhered in the decellularized testis ECM. By immunofluorescence, we verified the positive expression of HSD17B3, GDNF, ACRV-1, and TRIM-36, indicating their differentiation using RA in vitro, reinforcing the possibility of EB in male germ cell differentiation. Finally, recellularized testis ECM may be a promising tool for future new approaches for testicular cell differentiation applied to assisted reproduction techniques and infertility treatment. Abbreviations: ACRV-1: Acrosomal vesicle protein 1; ATB: Penicillin-streptomycin; DAPI: 4,6-Diamidino-2-phenylindole; EB: Embryoid bodies; ECM: Extracellular matrix; ESCs: Pluripotent embryonic stem cells; GAGs: Glycosaminoglycans; gDNA: Genomic DNA; GDNF: Glial cell line-derived neurotrophic factor; H&E: Hematoxylin and eosin; HSD17B3: 17-beta-Hydroxysteroid dehydrogenase type 3; PBS: Phosphate-buffered saline; PGCLCs: Primordial germ-cell-like cells; RA: Retinoic acid; SDS: Sodium dodecyl sulfate; SEM: Scanning electron microscopy; SSCs: Spermatogonial stem cells; TRIM-36: Tripartite Motif Containing 36;.
Keywords: Decellularized testicular matrix; embryonic stem cells; male infertility; reproduction